18F‐Fluoromisonidazole positron emission tomography/CT‐guided volumetric‐modulated arc therapy‐based dose escalation for hypoxic subvolume in nasopharyngeal carcinomas: A feasibility study. Issue 12 (30th September 2017) - Qiu, Jianjian; Lv, Bo; Fu, Meina; Wang, Xianglian; Zheng, Xiangpeng; Zhuo, Weihai
Abstract: Background: The purpose of this study is to investigate the feasibility of a simultaneously integrated boost to the hypoxic subvolume of nasopharyngeal carcinomas (NCPs) under the guidance of 18 F‐fluoromisonidazole (FMISO) positron emission tomography (PET)/CT using volumetric‐modulated arc therapy (VMAT) and intensity‐modulated radiotherapy (IMRT) techniques. Methods: Eight patients with NPC were treated with simultaneous integrated boost‐IMRT (treatment plan named IMRT70) with dose prescriptions of 70 Gy, 66 Gy, 60 Gy, and 54 Gy to the gross tumor volume (GTV), positive neck nodes, the planning target volume (PTV), and the clinically negative neck, respectively. Based on the same datasets, experimental plans with the same dose prescription plus a dose boost of 14 Gy (an escalation of 20% of the prescription dose) to the hypoxic volume target contoured on the pretreatment 18 F‐FMISO PET/CT imaging were generated using IMRT and VMAT techniques, respectively (represented by IMRT84 and VMAT84). Two or more arcs (approximately 2‐2.5 arcs, totally rotating angle <1000 degrees) were used in VMAT plans and 9 equally separated fields in IMRT plans. Dosimetric parameters, total monitor units, and delivery time were calculated for comparative study of plan quality and delivery efficiency between IMRT84 and VMAT84. Results: In experimental plans, hypoxic target volumes successfully received the prescribed dose of 84 Gy in compliance with other dose constraints with either the IMRT technique or the VMAT technique. In terms of the target coverage, dose homogeneity, and organs at risk (OAR) sparing, there was no statistically significant difference between the actual treatment plan of IMRT70 and experimental plans. The total monitor unit of VMAT84 (525.7 ± 39.8) was significantly less than IMRT70 (1171.5 ± 167; P = .001) and IMRT84 (1388.3 ± 151.0; P = .001) per fraction, with 55.1% and 62.1% reduction. The average machine delivery time was 3.5 minutes for VMAT plans in comparison with approximately 8 minutes for IMRT plans, resulting in a reduction factor of 56.2%. For experimental plans, the 3D gamma index average was over 98.0% with no statistical significant difference when a 3%/3 mm gamma passing rate criteria was used. Conclusion: With the guidance of 18 F‐FMISO PET/CT imaging, dose escalation to hypoxic zones within NPC could be achieved and delivered efficiently with the VMAT technique in comparison with the IMRT technique.